Chlamydia pneumoniae induces nitric oxide synthase and lipoxygenase- dependent production of reactive oxygen species in platelets - Kälvegren, Hanna; Bylin, Helena; Leanderson, Per; Richter, Arina; Grenegård, Magnus; Bengtsson, Torbjörn (Thrombosis and Haemostasis, 2005)
There is increasing evidence that Chlamydia pneumoniae is linked to atherosclerosis and thrombosis. In this regard, we have recently shown that C. pneumoniae stimulates platelet aggregation and secretion, which may play an important role in the progress of atherosclerosis and in thrombotic vascular occlusion. The aims of the present study were to investigate the effects of C. pneumoniae on platelet-mediated formation of reactive oxygen species (ROS) and oxidation of low-density lipoprotein (LDL) in vitro. ROS production was registered as changes in 2‘,7’-dichlorofluorescin- fluorescence in platelets with flow cytometry. LDL-oxidation was determined by measuring thiobarbituric acid reactive substances (TBARs). We found that C. pneumoniae stimulated platelet production of ROS. Polymyxin B treatment of C. pneumoniae, but not elevated temperature, abolished the stimulatory effects on platelet ROS- production, which suggests that chlamydial lipopolysaccharide has an important role. Inhibition of nitric oxide synthase with nitro-L-arginine, lipoxygenase with 5,8,11-eicosatriynoic acid and protein kinase C with GF 109203X significantly lowered the production of radicals. In contrast, inhibition of NADPH-oxidase with di-phenyleneiodonium (DPI) did not affect the C. pneumoniae induced ROS-production. These findings suggest that the activities of nitric oxide synthase and lipoxygenase are the sources for ROS and that the generation is dependent of the activity of protein kinase C. The C. pneumoniae-induced ROS-production in platelets was associated with an extensive oxidation of LDL, which was significantly higher compared to the effect obtained by separate exposure of LDL to C. pneumoniae or platelets. In conclusion, C. pneumoniae interaction with platelets leading to aggregation, ROS-production and oxidative damage on LDL, may play a crucial role in the development of atherosclerotic cardiovascular disease.
Keywords: Atherosclerosis; bacteria-cell interaction; oxygen radical; LPS; thrombosis